Mid‐elevation ecosystems of Panama: future uncertainties in light of past global climatic variability. (27th September 2016) - Correa‐Metrio, Alexander; Vélez, Maria I.; Escobar, Jaime; St‐Jacques, Jeannine‐Marie; López‐Pérez, Minerva; Curtis, Jason; Cosford, Jason
ABSTRACT: Modern changes in regional climates will result in high ecosystem turnover and substantial biodiversity rearrangements. Understanding these changes requires palaeoecological studies at temporal resolutions comparable to the time window at which modern climate change is occurring. Here we present a multi‐proxy, high‐resolution record of forest and lake ecosystem change that occurred during the last 1100 years at middle elevations in Panama. From ∼900 to 1400 CE, regional forest and lake ecosystems were characterized by high seasonality, probably associated with both high El Niño activity and higher global temperatures. At ∼1400 CE, an abrupt transition marked the decoupling of forest and lake responses, with forest responding mostly to local patterns of human occupation, and lake trophic status being controlled mostly by the regional precipitation–evaporation balance, possibly associated with solar irradiance. Factors that played important roles in shaping regional ecosystems during the last 1100 years will probably again play critical roles within the coming decades, i.e. higher precipitation seasonality and higher temperatures. Past responses of the system, together with pervasive human activities, suggest that future conditions will simplify mid‐elevation forests. Given the importance of these geographical locations as hotspots of biological diversity, substantial losses of global biodiversity are foreseen.